Forecasting of tourism demand of Sarawak using winters' three parameter exponential smoothing method - 499168 Ho, Mee Chyong; Zuhaimy Ismail; Fakulti Sains (2011)
Project Paper (Sarjana Muda Sains serta Pendidikan (Matematik)) - Universiti Teknologi Malaysia, 2011